Hubungan Kadar Interleukin-6 terhadap Luaran Mortalitas dan Hari Rawat serta Hari Penggunaan Oksigenasi Tekanan Positif Pasien COVID-19 di RSUP Dr. Sardjito - Kuncoro, Kusuma Edhi; Sudadi; Sari, Djayanti; Wisudarti, Calcarina Fitriani Retno (Jurnal Komplikasi Anestesi, 2021)
Background: COVID-19 is a disease caused by the SARS-CoV-2 virus with the main clinical manifestations of respiratory disorders. Patients with severe and critical symptoms require oxygenation therapy during treatment. Interleukin-6 (IL-6) plays a role in the course of the disease and is associated with the clinical severity of COVID-19. IL-6 has the potential as one of the test parameters to estimate the outcome of COVID-19 patients. Objective: To know the relationship between IL-6 levels and the outcome of mortality, length of stay (LOS) and positive pressure oxygenation days of COVID-19 patients during hospitalization at Dr. Sardjito hospital. Methods: The study design was a retrospective observational cohort by taking secondary data from the medical records of hospitalized COVID-19 confirmed patients who were examined for serum IL-6 during April 2020- March 2021 at dr.Sardjito Hospital. Data collection was carried out at the Medical Records Instalation of Dr. Sardjito Hospital. The relationship of the IL-6 variable to the outcome was tested by logistic regression method and further analyzed with Kaplan-Meier and Cox regression analysis of survival. Results: There were 302 research subjects with a mean age of 55.45 (+14.79) years, 183 male (60.6%) and 119 female (39.4%). Subjects with IL-6 >80 pg/mL had a higher risk of death than those with IL-6 <80 (p=0.000, HR=4.68). As many as 87.4% of the subject required oxygenation therapies during hospitalization. Group of subjects with an IL-6 value >80 was significantly required more positive pressure oxygenation therapy (p=0.000) and require longer (p=0.005) duration of positive pressure oxygenation (9.36(+5,9) days) compared to the group of subjects with IL-6 <80 (6(+2,98) days). The difference in LOS was significantly different between groups of subjects, with the median LOS for subjects with IL-6 >80 was 25 days, while for subjects with IL-6 <80 was 13 days (p= 0.000). Conclusion: There was a significant relationship of IL-6 levels >80 pg/mL with increased risk of mortality, LOS and the requirement of positive pressure oxygenation therapies in COVID-19 patients.